2018
DOI: 10.1002/joc.5925
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns, trends and teleconnection of cumulative rainfall deficits across Central America

Abstract: Central America is a region vulnerable to hydrometeorological threats. Recently, the impacts of droughts caused higher economic losses in comparison to, for example, floods and landslides. This study focuses on the spatio‐temporal behaviour of cumulative rainfall deficits across Central America attempting to provide an historical context to the most recent drought episodes. We developed a long‐term (1950–2014), monthly rainfall data set that merged large‐scale interpolated products with a station observation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
5
29
0
1
Order By: Relevance
“…Guevera-Murua et al (2018) reported a similar influence of the ENSO in Guatemala, cold phases were related to wet periods and warm phases were related to dry periods. Figure 7 showed that the relationship between the ENSO and the SPI-12 was inverse for the basin, however it also showed that there could be some others events involved in this relationship (Muñoz-Jiménez et al, 2019). This behaviour could be associated to the seasonal ENSO-PDO relation and to its influence on the Mexican climate;…”
Section: Spi-12) Tuvieron Diferencias Notables (Figuras 4 Y 5)mentioning
confidence: 94%
See 2 more Smart Citations
“…Guevera-Murua et al (2018) reported a similar influence of the ENSO in Guatemala, cold phases were related to wet periods and warm phases were related to dry periods. Figure 7 showed that the relationship between the ENSO and the SPI-12 was inverse for the basin, however it also showed that there could be some others events involved in this relationship (Muñoz-Jiménez et al, 2019). This behaviour could be associated to the seasonal ENSO-PDO relation and to its influence on the Mexican climate;…”
Section: Spi-12) Tuvieron Diferencias Notables (Figuras 4 Y 5)mentioning
confidence: 94%
“…Climate change will not affect everyone to the same degree; developing countries and the most vulnerable social groups will be the most affected (Mateos et al, 2016). In the Mesoamerican and Caribbean regions, challenges in this regard are growing Muñoz-Jiménez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonequilibrium processes under an unsaturated condition below the cloud base, enhance the net transfer of water molecules from the falling drops to the surrounding air (Crawford, Hollins, Meredith, & Hughes, 2017;Graf, Wernli, & Sodemann, 2018;Kong & Pang, 2016;Salamalikis, Argiriou, & Dotsika, 2016), resulting in enriched surface rainfall. The latter process is a potential common feature within the CADC, whereby recent warm ENSO-induced droughts decreased rainfall amounts and intensities as well as promoting more intense warming and unsaturated atmosphere conditions during rainfall events (Jimenez et al, 2018;Muñoz-Jiménez et al, 2019).…”
Section: Potential Mean Recharge Elevation and Rainfall-groundwatermentioning
confidence: 99%
“…In Central Costa Rica, our high-resolution rainfall isotope data are unique in the sense that they comprise ENSO's neutral, warm (very strong and weak), and cold (moderate) phases. In general, warm ENSO events result in a large rainfall deficit across the Pacific slope of Central America and a surplus over the Caribbean slope (Sánchez-Murillo et al, 2017b;Muñoz-Jiménez et al, 2019). Variations in rainfall distribution patterns are a response of ENSO driven anomalous ITCZ migrations (Adam et al, 2016) and moisture transport modulation (Durán-Quesada et al, 2017).…”
Section: El Niño/southern Oscillation Modes and Isotope Variabilitymentioning
confidence: 99%